Dual cellular-path (MIHP) healthy urbanism - a proactive means to sustain placemaking - Hsu, Li-Yen (Edelweiss Applied Science and Technology, 2023)
The importance of holistic information integrity in managing complex problems and fostering inclusive, healthy urban environments has garnered significant attention. Distributing artificial intelligence-based topologies with dual or plural sensor-information nodes improves availability, reliability, and maintainability (ARM), ensuring holistic information integrity and promoting safe, efficient living. Bipartite spider-webs and cube-connected cycles target "the radial-ring urban-building skeleton" and "wetlands and sparsely populated areas," respectively. Also, honeycomb tori, also known mathematically as HT(m), m≥2, or a type of generalized honeycomb tori, GHT(m, 6m, 3m), have been discovered to have two Hamiltonian paths (MIHP) that are not connected to each other. Wireless communications tasks use these paths. This parallelism can create dual cipher-coding to support sensitive logistic privacy and help prevent information loss, electromagnetic interference, and unexpected changes caused by such things as clogged water. Consequently, the aforementioned methods can engage stakeholders by providing comprehensive and reliable information, fostering strong accountability, and ensuring the welfare of future generations. We can adapt this forward-thinking urbanism to areas that enhance life values, particularly in security-sensitive regions such as the acknowledged battlefield Kinmen. Here, the scalable parallelism topology aims to prevent harmful illness or substance spread, prevent sensitive or unnecessary challenges, and positively engage place-making through reliable communications and monitoring.